Sport for Development in South America: A Comparison Between Argentina, Chile, and Uruguay - Soto-Lagos, R (Taylor and Francis, 2024)
In the last decade in Argentina, Chile, and Uruguay, an alternation in the national administration of the state could be observed. What society schematically considers “progressive” governments have changed. In each case, government plans were defined where the goals were established, as well as the programs that marked national sports policies. In this context, the objective of this work was to analyse and compare the guidelines defined by the national states to build the “sport for development” in the national sports plans. The results show that in the different countries particular meanings were focused. Namely, in Argentina social sport is presented as an inclusive practice in terms of rights. In Chile, recreational sport is presented as a right and above all it is linked to a health discourse. In Uruguay: community sports-they were taking a greater role in national sports policies hand in hand with the guidelines of international organisations as well as the demand of local actors. Each country assumes its own focus on translating the concept of “sport for development”. However, there are similarities between the three nations that are explained by the neoliberal conception of the state. © 2024 selection and editorial matter, Billy Graeff, Simona Šafaříková and Lin Cherurbai Sambili-Gicheha.